Basiswoordeboek van Afrikaans - Otto, A.N. (Lexikos, 1995)
This, the Basiswoordeboek van Afrikaans (BA), is the first appearance of an Afrikaans learner’s dictionary in South Africa. It is aimed especially at learners who are attempting to master Afrikaans as a second, third or fourth language. Since the vocabulary is confined to a very elementary level, a wide variety of users should be able to understand it. The restriction of the macrostructure causes a number of problems, which are pointed out. BA is a user-friendly dictionary in which information can generally be retrieved easily. Pronunciation guidance is confined to problematical words. Potential spelling errors are brought to the users’ attention through text boxes. Explicit morphological and syntactic guidance are given and this ensures that information can instantly be retrieved. Adequate syntactic guidance is also provided by means of example sentences and text boxes. The definitions given are understandable because they consist of short, complete sentences that are based on naturally spoken and written Afrikaans. The meaning of lexical items is explained in context and in most cases the definiens also provides an illustration of the lemma in its typical grammatical context. Semantic relationships like polysemy, homonymy, synonymy and antonomy are given more attention than that received in the Afrikaans explanatory dictionaries. It is especially BA’s example sentences and text boxes which provide the necessary usage guidance to facilitate encoding. All in all, BA can help to improve the communicative ability of foreign language speakers of Afrikaans who wish to master Afrikaans.